(untitled) (Bangladesh Journal of Medical Science, 2024)
In Malaysia, colorectal cancer is the second most common cause of cancer. Early detection through screening programmes is one of the most important public health initiatives in reducing cancer-related death. For decades, Malaysia has a colorectal cancer screening program in government-funded primary care facilities. However, screening uptake is minimal and numerous theories have been postulated. The aim of this article is to explore the possible reasons for low colorectal screening uptake among primary care physicians. Bangladesh Journal of Medical Science Vol. 23 No. 01 January’24 Page : 278-280